Cytosolic iron‐sulphur protein assembly is functionally conserved and essential in procyclic and bloodstream Trypanosoma brucei. Issue 5 (23rd July 2014) - Basu, Somsuvro; Netz, Daili J.; Haindrich, Alexander C.; Herlerth, Nils; Lagny, Thibaut J.; Pierik, Antonio J.; Lill, Roland; Lukeš, Julius
Summary Cytosolic and nuclear iron‐sulphur (Fe/S) proteins include essential components involved in protein translation, DNA synthesis and DNA repair. In yeast and human cells, assembly of their Fe/S cofactor is accomplished by the CIA (cytosolic iron‐sulphur protein assembly) machinery comprised of some 10 proteins. To investigate the extent of conservation of the CIA pathway, we examined its importance in the early‐branching eukaryote Trypanosoma brucei that encodes all known CIA factors. Upon RNAi‐mediated ablation of individual, early‐acting CIA proteins, no major defects were observed in both procyclic and bloodstream stages. In contrast, parallel depletion of two CIA components was lethal, and severely diminished cytosolic aconitase activity lending support for a direct role of the CIA proteins in cytosolic Fe/S protein biogenesis. In support of this conclusion, the T. brucei CIA proteins complemented the growth defects of their respective yeast CIA depletion mutants. Finally, the T. brucei CIA factor Tah18 was characterized as a flavoprotein, while its binding partner Dre2 functions as a Fe/S protein. Together, our results demonstrate the essential and conserved function of the CIA pathway in cytosolic Fe/S protein assembly in both developmental stages of this representative of supergroup Excavata.